Chapter 7 Where is My State? Citizenship as a Factor in Yugoslavia's Disintegration - Štiks, Igor (Bloomsbury Academic, 2015)
Chapter 7 shows that citizenship has to be counted as one of the crucial factors of Yugoslavia's disintegration. The fundamental questions of citizenship related to the very definition of membership in a political community as well as the citizenship contract by which citizen exchanges his loyalty and duties for the rights and protection by his political community and its institutions (state) influenced critically the democratization process and Yugoslavia's disintegration. At the crucial junction, in the context of imminent redefinition and possible collapse of federal Yugoslavia, between early 1990 and early 1992, citizens were asking themselves these basic questions: To what political community do I belong? or, to whom do I owe my loyalty? And, finally, who (what state?) guarantees, or promises to guarantee my rights - starting with human, civic and political rights, employment and property ... - and, last but not least, security? The ethnonational conception of citizenship, the chapter argues, finally prevailed and fuelled conflicts over the redefinition of borders within which the ethnonational states were to be formed on the basis of absolute majorities of the core ethnonational groups.